Application of Archimedes' Law with Eggs as a Medium to Improve the Understanding of Fourth Grade Students at SD Negeri 07 Sungayang - Kayana Tantri (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2025)
The Community Service Program KKN conducted in Sungayang District is one of the implementations of the Tri Dharma of Higher Education in the field of community service, particularly in primary education. This article aims to describe the application of Archimedes’ Principle using a simple medium, namely eggs, to improve the understanding of fourth-grade students at SD Negeri 07 Sungayang. The study employed an experimental method with a pretest–posttest design involving 19 students as research subjects. The learning process consisted of four stages: preparation, pretest, experimental activities, and posttest. The findings indicate an improvement in students’ understanding, with the average pretest score of 51,6 increasing to 74,2 in the posttest, showing an average gain of 22,6 points. In addition to cognitive improvement, students also displayed greater enthusiasm, active participation, and confidence during the learning process. These results are consistent with constructivist learning theory and Piaget’s theory of cognitive development, which emphasize the importance of concrete experiences in understanding abstract concepts. Therefore, the use of eggs as a simple learning medium has proven effective as an alternative strategy for teaching science in primary schools, especially in contexts with limited laboratory facilities.